Including processed poultry and porcine by‐products in diets high in plant ingredients reduced liver TAG in Atlantic salmon, Salmo salar L. (17th October 2014) - Liland, N.S.; Hatlen, B.; Takle, H.; Venegas, C.; Espe, M.; Torstensen, B.E.; Waagbø, R.
Abstract The effects on Atlantic salmon (Salmo salar L.) metabolic health of including modern processed land animal by‐products (LAP) to a plant‐ and marine‐based diet (50% marine and 50% plant ingredients) were investigated. Three experimental diets were made with systematic replacements of both marine and plant ingredients with LAP as a source of protein (poultry meal and porcine blood meal) and fat (poultry oil) to fit a two‐way factorial design. A 16‐week feeding trial was performed with postsmolts in seawater (initial weight 372 g). The diet with both protein and lipids from LAP reduced liver triacylglycerols more than fourfold compared to the diet without LAP. This was confirmed by histological examinations showing reduced fatty degeneration in the liver of fish fed the high LAP diet. No severe negative effects on gut or tissue health were seen by histological examinations or by measuring genetic markers with qPCR, although a trend in the histological results indicated an improved gut health by including LAP in the diets. Clinical analyses of plasma and lipoprotein fractions showed no differences between dietary groups.